Microbial challenges and solutions in root canal therapy - Ajmi, Norah Fahad Al; Alshenaifi, May Khalid; Binsalem, Mada Mohammed; Alahmary, Khalid Abdullah; Shahrani, Noha Abdullah Al; Alasim, Abdulrahman Mohammed; Alotaibi, Fahad Rashed; Ali, Abdulwahab Saleh; Attar, Sameeh Mansour; Shahrani, Nourah Mobarek Al (International Journal Of Community Medicine And Public Health, 2024)
Root canal therapy (RCT) faces significant challenges due to microbial invasion and biofilm formation within the root canal system. The intricate anatomy of root canals, including isthmuses, lateral canals, and apical deltas, provides a conducive environment for pathogenic microorganisms, complicating effective disinfection. Key pathogens such as Enterococcus faecalis and Candida albicans are highly resilient, capable of forming biofilms that protect them from antimicrobial agents and host defences. Current antimicrobial strategies in endodontics combine mechanical instrumentation with chemical disinfection. Mechanical debridement, though essential, often falls short of thoroughly cleaning the complex root canal anatomy. Sodium hypochlorite (NaOCl), the gold standard irrigant, exhibits broad-spectrum antimicrobial properties but struggles to penetrate biofilms and dentinal tubules fully. Adjunctive solutions like chlorhexidine (CHX) and ethylenediaminetetraacetic acid (EDTA) enhance the antimicrobial efficacy of NaOCl by providing prolonged action and removing the smear layer, respectively. Intracanal medicaments, such as calcium hydroxide (Ca(OH)2), are utilized to maintain antimicrobial activity between treatment sessions. Despite its high pH and effectiveness against a wide range of bacteria, Ca(OH)2 shows limited efficacy against biofilm-forming bacteria like Enterococcus faecalis. Innovations in irrigation techniques, such as passive ultrasonic irrigation (PUI) and laser-activated irrigation (LAI), have improved the delivery and activation of irrigants, enhancing their ability to disrupt biofilms and penetrate the root canal system. Nanoparticle-based irrigants and medicaments represent a promising advancement in endodontic disinfection. Their small size and large surface area allow for better penetration and interaction with bacterial cells, significantly reducing bacterial load in the root canal system. Combining traditional and advanced antimicrobial strategies is essential for overcoming the limitations of current methods and improving the success rates of endodontic therapy. Understanding the mechanisms of microbial invasion and biofilm formation, along with integrating emerging technologies, can lead to more effective disinfection protocols. This approach aims to enhance treatment outcomes and ultimately ensure the longevity of endodontically treated teeth.